Efektivitas Edukasi Gizi terhadap Penurunan Berat Badan pada Remaja Obesitas - Kiki Arianti; Rizki Amalia Putri (Journal of Applied Health Sciences, 2025)
Adolescent obesity is a growing public health problem that contributes to the risk of degenerative diseases in adulthood. One of the effective interventions to address obesity is nutrition education, which aims to improve adolescents’ knowledge and skills in selecting and consuming healthy foods. This study aimed to analyze the effectiveness of nutrition education in reducing body weight among obese adolescents. A quasi-experimental design with a pre-test and post-test approach was employed in the intervention group. The sample consisted of 40 obese adolescents selected using purposive sampling. The nutrition education intervention was conducted for 8 weeks through interactive lectures, group discussions, and individual counseling sessions, covering topics such as balanced nutritional needs, portion control, healthy food selection, and the importance of physical activity. Body weight was measured before and after the intervention and analyzed using a paired t-test. The results showed a significant decrease in body weight in the intervention group (p < 0.05), with an average reduction of 2.3 ± 0.8 kg. These findings indicate that structured and continuous nutrition education can be an effective strategy for reducing body weight in obese adolescents. This study recommends integrating nutrition education programs into school and community activities as part of efforts to prevent and control adolescent obesity.